Epidemiological implications of multiple pregnancy in public health - Lacunza Paredes, Rommel Omar (2015)
Multiple gestation pregnancy rates have increased in recent years possibly related to socio-demographic factors including deferral of motherhood and some medical factors like fertility treatments. Associated complications including prematurity, cerebral palsy, hypertensive disease of pregnancy, hyperemesis, gestational diabetes have also increased.